THE IMPACT OF CLIMATE DISASTERS ON POVERTY VULNERABILITY OF RURAL HOUSEHOLDS IN EAST JAVA PROVINCE 2016 - Dian Priastiwi (SEAN Institute, 2023)
The study aims to analyze the effect of climate disasters on the vulnerability rural households to poverty in East Java. Vulnerability is defined as probability of a household becoming poor on the future by using the per capita expenditure function of the household. This approach will produce a household vulnerability to poverty score that is used to analyze the effect of climate disasters on vulnerability to poverty. The results, it is known that East Java province has a very low average score of poor vulnerability (vulnerability to poverty score of VEP < 0,5). Sidoarjo regency and Surabaya city are the regions with the lowest poor vulnerability rate in East Java province, while the highest poor vulnerability rate is in Bangkalan Regency. The variable of flood disaster has an impact on the vulnerability of poor households, while landslide and tornado events have not been proven to affect the vulnerability of poor households in East Java province.